2017
DOI: 10.1016/j.jretconser.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Does innovation-orientation lead to retail industry growth? Empirical evidence from patent analysis

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 43 publications
(77 reference statements)
1
66
0
8
Order By: Relevance
“…Apesar disso, as patentes trazem vantagens oportunas e tem sido amplamente utilizada sem pesquisas acadêmicas, estratégias de Pesquisa & Desenvolvimento e estudos de gestão tecnológica (Ardito, 2017). Como apresentado por Pantano (2017), as patentes provem informações detalhadas sore a tecnologia, incluindo atributos técnicos e de Mercado, critérios de originalidade e detalhes sobre o inventor. Patentes também cobrem um campo de inovações ao longo de diferentes países por longos períodos de tempo (Park et al, 2005).…”
Section: Análise De Patentesunclassified
“…Apesar disso, as patentes trazem vantagens oportunas e tem sido amplamente utilizada sem pesquisas acadêmicas, estratégias de Pesquisa & Desenvolvimento e estudos de gestão tecnológica (Ardito, 2017). Como apresentado por Pantano (2017), as patentes provem informações detalhadas sore a tecnologia, incluindo atributos técnicos e de Mercado, critérios de originalidade e detalhes sobre o inventor. Patentes também cobrem um campo de inovações ao longo de diferentes países por longos períodos de tempo (Park et al, 2005).…”
Section: Análise De Patentesunclassified
“…Currently, many firms are actively applying for patents with economic value and their competing patents increasingly tend to converge with technologies in other fields; for these reasons, patent analysis studies have been used to forecast technology success [36], monitor emerging technologies [37] and identify the relationship between innovation-orientation and industry growth [38]. Therefore, our patent-based competitive intelligence would help technology planners monitor competition trends in augmented reality and understand the technology strategies of competing firms.…”
Section: Augmented Reality: Technical Overview and The Potential As Amentioning
confidence: 99%
“…They analyzed the patent citations from patent documents by supervised learning approach [19]. In the retail field, research related to an innovation leading to retail industry growth was carried out by Pantano et al (2017). The study showed an empirical evidence of the growth from the results of patent analysis [32].…”
Section: Patent Analysis and Technology Forecastingmentioning
confidence: 99%
“…In the retail field, research related to an innovation leading to retail industry growth was carried out by Pantano et al (2017). The study showed an empirical evidence of the growth from the results of patent analysis [32]. Caviggioli (2016) used the international patent classification (IPC) codes extracted from the patent documents for technology fusion.…”
Section: Patent Analysis and Technology Forecastingmentioning
confidence: 99%